Pegada de carbono do melão produzido em sistema convencional ou conservacionista - Barros, Viviane da Silva (Universidade Federal Rural do Semi-Árido, 2015)
This study evaluates the environmental impact of melon production systems on climate change, integrating the research lines of the Brazilian Agricultural Research Corporation (Embrapa). It is the result of partnership held among Embrapa - Tropical Agroindustry, the Federal Rural University of Semi-Arid (UFERSA), and the University of Massachusetts (UMass). The research is based on an evaluation of the product life cycle (melon), focusing on climate change impact category. The study was conducted in two stages, one held in Brazil, in 2011, and the second, in the US, between 2014 and 2015. In Brazil, data were collected in the experimental area located in Agricola Famosa farm, located in the municipality of Tibau, RN, with order to determine the efficiency of farming systems practiced today (conventional) and conservation, based on the use of green manure. In the conventional system, the melon (Goldex) was cultivated after the merger of spontaneous vegetation and conservation system, after overturning or incorporation of plant biomass from the green manure with maize intercropped with braquiária and Guandu beans. The product system refers to melon production in Brazil covered production in conventional and conservation systems considering the following processes: production of green fertilizers seeds and melon, biomass production of green manure production melon seedlings production melon field, packaging and transport of melons to Europe, as well as production and transportation of supplies for the experimental area. The stage of the research conducted in the United States sought to determine the conventional cultivation system efficiency currently practiced in the experimental farm of UMass. Thus, this product system included the production of seeds and melon seedlings production in melon field, packaging and transport of melon, production and transport of inputs for the experimental area of UMass. In Brazil, the best result of carbon footprint was the conservationist corn intercropping system with braquiária with incorporation that generates an average carbon footprint of 647.82 CO2-eq / t melon, while the footprint of Brazilian conventional system is 756, 90 kg CO2-eq / t. Detailing the process, we observe that the change of land use and melon transportation Port of Pecém, CE, to the port of Rotterdam, in the Netherlands, are the processes that most contribute to the carbon footprint of melon produced in Brazil. The change of land use, due to the increasing number productive melon areas in Northeast Brazil, including Jaguaribe-Açu polo, we consider the emissions for the transformation of land with scrub vegetation to melon producing area. In the US, the footprint is 356 kg CO2-eq/t, and the packaging process is the largest contributor to this result. It is important to note that the land use change impact was not considered in the US, because this change has occurred more than 20 years ago on the farm UMass. We conclude that in terms of environmental efficiency, the best result in Brazil occurs in the conservation system, showing that green manure increases soil organic matter, thus reducing the carbon footprint. In order to reduce the footprint of Brazilian melons, making it as competitive as the US, it is necessary to held to melon production in agricultural areas with natural vegetation removed for more than 20 years before. The results of this research subsidize actions to improve the competitiveness of Brazilian melons front of potential non-tariff barriers related to reducing emissions of greenhouse gases by agriculture and adoption of low carbon practices
Melon carbon Footprint produced in conventional or conservation system
Keywords: Melon; Environmental impact; Greenhouse gases; Climate changes; Melão; Impacto ambiental; Gases de efeito estufa; Mudanças climáticas; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA